The Development of a System for Online Appointment Referral Card in Outpatient Department, Omkoi Hospital - Reankongngern, Wanlop; Samutwet, Channuwatpong (Journal of Nursing and Public Health Research, 2022)
The objectives of this participatory action research were to develop a system for online appointment referral card in outpatient department, Omkoi Hospital, Omkoi District, Chiang Mai Province. Participants were 26 health care providers (nurses and public health academics) from 11 public health service centers and 36 patients in Omkoi District. The research instrument was a system for online appointment referral card that was developed from all participants. The data collection tools were the satisfaction assessment form from health care providers and patients after applying the system. The data were analyzed using descriptive statistics (frequency, percentage, mean and standard deviation). The qualitative data was analyzed using content analysis. The results found that a system for online appointment referral card consisted of four steps. Step one was that an appointment date of patients in a tertiary hospital. Step two was that a health care provider in a community hospital recorded patient information in the online referral system and informed patient information to a health care provider in a primary care setting. Step three was that patients received an appointment card with a health care provider in their primary care setting. Step 4 was that patients went to see a doctor for following up at a tertiary hospital. The mean scores of satisfaction of health care providers and patients after applying this system were 4.13 and 4.31, respectively. Moreover, health care providers and patients agreed that this system was helpful. They suggested to apply this system in the long term. It can be concluded that both health care providers and patents had higher satisfaction with this developed system and should be used it continuously in order to improve the information networks between health care services.